STRATEGI KOMUNIKASI KONSELING DALAM MENGINTERNALISASIKAN MODERASI BERAGAMA DI SEKOLAH - Ahmad Khairul Nuzuli; Shinta Ayu Khirani; Silvy Yulizar Putri; Suci Utami Rahmadani; Wiwit Wahyuni; Zonil Sandra P. (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this research is to see how Guidance and Counseling teachers build awareness of religious moderation in the school environment. In this study using interpersonal communication, qualitative descriptive with a case study approach, and data collection techniques, namely by interview techniques. The results of the study found that counseling communication strategies in internalizing religious moderation in schools can be applied by socializing to each locale, providing information services with interpersonal communication, providing Group Guidance Services to students.